Extant Genus in the Mesozoic: Paleoplatyura Meunier (Diptera: Keroplatidae) Found in the Cretaceous Amber of Myanmar - Ševčík, Jan; Krzemiński, Wiesław; Skibińska, Kornelia (Insects, 2021)
Three new species of Paleoplatyura Meunier, 1899, i.e., Paleoplatyura agnieszkae sp. nov., P. miae sp. nov., and P. magnifica sp. nov., are described and figured. The concept of the genus is briefly discussed, and its systematic position is clarified. A key to fossil species is provided. The genus Paleoplatyura is described from the Eocene Baltic amber. It is concluded that, in Baltic amber, this group is represented only by the type species, and the identity of the other two species is problematic. No additional specimens have been found so far in this amber. Therefore, the presence of as many as three new species in Burmese amber, certainly belonging to Paleoplatyura, is a confirmation of its occurrence already in the Mesozoic.
Keywords: inclusions; taxonomy; fossil insects; Bibionomorpha; Mesozoic; Sciaroidea